1992
DOI: 10.1002/bjs.1800790330
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant tissue-type plasminogen activator is superior to streptokinase for local intra-arterial thrombolysis

Abstract: The results of local intra-arterial thrombolysis in 98 patients treated with streptokinase and 69 patients treated with recombinant tissue plasminogen activator (rtPA) have been compared. The two groups of patients were well matched and their treatment protocols were identical except with regard to the thrombolytic agent used. Strict criteria for defining successful thrombolysis were used. Successful lysis was achieved in 40 of 98 patients (41 per cent) receiving streptokinase and 40 of 69 patients (58 per cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…A pilot trial with rt-PA suggested that an infusion rate of 3 or 5 mg/h produced similar results as 10 mg/h [11]. Similar infusion rates (0.1 and 0.05 mg/kg per hour) were tested in the trial evaluating surgery vs thrombolysis for ischaemia of the lower extremity (STILE), but in other countries lower infusion rates (e. g. 0.5 or 1.0 mg/h) are being advocated [12][13][14]. An interrelationship between infusion rate, duration of lysis and risk of bleeding is not firmly established in peripheral arterial thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot trial with rt-PA suggested that an infusion rate of 3 or 5 mg/h produced similar results as 10 mg/h [11]. Similar infusion rates (0.1 and 0.05 mg/kg per hour) were tested in the trial evaluating surgery vs thrombolysis for ischaemia of the lower extremity (STILE), but in other countries lower infusion rates (e. g. 0.5 or 1.0 mg/h) are being advocated [12][13][14]. An interrelationship between infusion rate, duration of lysis and risk of bleeding is not firmly established in peripheral arterial thrombolysis.…”
Section: Discussionmentioning
confidence: 99%
“…Lansdale et al performed a nonrandomized comparative trial examining the effects of intraarterial streptokinase and tPA with arterial occlusion. 12 Rates of amputation and death were lower in tPA-treated patients (41% vs 59%), along with a shorter time to lysis (22 hours vs 40 hours). Since the STILE and TOPAS trials, a consensus proposal by a Working Group including angiologists, hematologists, interventional radiologists, and vascular surgeons from North America and Europe proposed that thrombolytic treatment should be considered as an acceptable treatment option in patients with acute arterial occlusion in native vessel or in bypass grafts.…”
Section: Tpa and Its Role In The Treatment Of Peripheral Vascular Dismentioning
confidence: 85%
“…It has been shown that SK yields a lower success rate (41 vs. 58%) than urokinase and tissue olasminogen activator (tPA) (1,5). Cost constraints lave so far kept us from using these drugs.…”
Section: Discussionmentioning
confidence: 99%